1997
DOI: 10.1063/1.366193
|View full text |Cite
|
Sign up to set email alerts
|

Effects of deposition temperature on the properties of hydrogenated tetrahedral amorphous carbon

Abstract: The properties of hydrogenated carbon films deposited from a highly ionized hydrocarbon plasma beam are studied as a function of deposition temperature. At low temperatures, the films have high sp3 bonding, density, and compressive stress and are very smooth. Two transition temperatures are observed, a lower transition T1 around 250 °C, dependent on ion energy, due to graphitization of C–C bonds, and a higher one T2 at about 450 °C due to the loss of hydrogen. The roughness rises at T1 and falls above T2. Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
38
1

Year Published

1999
1999
2013
2013

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 132 publications
(45 citation statements)
references
References 67 publications
6
38
1
Order By: Relevance
“…Nevertheless increasing the sp 2 content is still expected to increase the cluster size and decrease the gap. As noted earlier, many authors 6,8,12,13,25 have put forward the hypothesis that the Lorentzian line shape arises from exchange narrowing and that the reduction in the linewidth as the sp 2 content increases is associated with the greater delocalization of the unpaired electrons as the cluster size increases. It should be noted, however, that it is the increased overlap of the wave functions brought about by the greater delocalization rather than the greater delocalization itself which increases the strength of the exchange interaction.…”
Section: B Analysis Of Linewidth Variation For V B ð100 Vmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless increasing the sp 2 content is still expected to increase the cluster size and decrease the gap. As noted earlier, many authors 6,8,12,13,25 have put forward the hypothesis that the Lorentzian line shape arises from exchange narrowing and that the reduction in the linewidth as the sp 2 content increases is associated with the greater delocalization of the unpaired electrons as the cluster size increases. It should be noted, however, that it is the increased overlap of the wave functions brought about by the greater delocalization rather than the greater delocalization itself which increases the strength of the exchange interaction.…”
Section: B Analysis Of Linewidth Variation For V B ð100 Vmentioning
confidence: 99%
“…Whether the film is a-C:H, ta-C:H, or ta-C, the decrease in ⌬B pp , in this higher bias region, is always accompanied by a decrease in the optical gap and an increase in the sp 2 fraction; 8-13 a correlation of linewidth and gap has already been noted. 25 Regarding the gap, Robertson and O'Reilly 2 showed that the most stable arrangement of sp 2 sites is in compact clusters of fused six- fold rings and that the gap varies inversely as the cluster size. This model was later modified 26 to account for the reduction in clustering produced by disorder and the presence of olefinic chains as well as aromatic rings.…”
Section: B Analysis Of Linewidth Variation For V B ð100 Vmentioning
confidence: 99%
“…The roughness of DLC films has been shown to depend on the various deposition methods 163,164 and deposition parameters such as ion energy, [165][166][167][168][169][170] gas mixture 163 and bias voltage. 169 Coating roughness is also dependent on substrate material [171][172][173] and the underlying substrate roughness.…”
Section: Dlc Reviewmentioning
confidence: 99%
“…This variation in elastic behaviour cannot be described by a stress induced phase transition from sp 2 to sp 3 bondings which is observed for deposition of amorphous carbon at room temperature. It is well described by the subplantation process [21][22][23]. As Sattel et al could show [23], heating the substrate to temperatures over about 250 °C prevents the film material to become diamond-like.…”
Section: Resultsmentioning
confidence: 99%